2020
DOI: 10.1126/scitranslmed.aax3063
|View full text |Cite
|
Sign up to set email alerts
|

ROR2 blockade as a therapy for osteoarthritis

Abstract: Osteoarthritis is characterized by the loss of the articular cartilage, bone remodeling, pain, and disability. No pharmacological intervention can currently halt progression of osteoarthritis. Here, we show that blocking receptor tyrosine kinase–like orphan receptor 2 (ROR2) improves cartilage integrity and pain in osteoarthritis models by inhibiting yes-associated protein (YAP) signaling. ROR2 was up-regulated in the cartilage in response to inflammatory cytokines and mechanical stress. The main ligand for RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 79 publications
2
40
0
Order By: Relevance
“…OA is mainly caused by mechanical overload ( Glyn-Jones et al, 2015 ), and it has been reported that YAP is both necessary and adequate to preserve cartilage homeostasis in OA ( Deng et al, 2018 ; Zhang Q. et al, 2019 ). A few recent studies demonstrated that suppressing YAP activity is effective in attenuating OA progression ( Gong et al, 2019 ; Thorup et al, 2020 ; Zhang et al, 2020 ). However, research is still lacking on how the mechanical forces, especially compression and hydrostatic pressure, regulate Hippo-YAP/TAZ pathway in chondrocytes in healthy cartilage and during OA development.…”
Section: Mechanoregulation Of Yap/taz In Human Diseasesmentioning
confidence: 99%
“…OA is mainly caused by mechanical overload ( Glyn-Jones et al, 2015 ), and it has been reported that YAP is both necessary and adequate to preserve cartilage homeostasis in OA ( Deng et al, 2018 ; Zhang Q. et al, 2019 ). A few recent studies demonstrated that suppressing YAP activity is effective in attenuating OA progression ( Gong et al, 2019 ; Thorup et al, 2020 ; Zhang et al, 2020 ). However, research is still lacking on how the mechanical forces, especially compression and hydrostatic pressure, regulate Hippo-YAP/TAZ pathway in chondrocytes in healthy cartilage and during OA development.…”
Section: Mechanoregulation Of Yap/taz In Human Diseasesmentioning
confidence: 99%
“…ROR2 inhibition in primary human chondrocytes suppressed expression of ADAMTS4/5 and increased SOX9. Furthermore, blocking ROR2 in a mouse OA model reduce pain and cartilage damage 35 . This study suggests that ROR2 is associated with WNT5A and hypertrophy and thus, ROR2 could also be a potential target for OA.…”
Section: Receptor Tyrosine Kinase-like Orphan Receptormentioning
confidence: 99%
“…On the other hand, if the diagnosis is made early, developing treatments to slow the progression of joint degradation is a reasonable goal. Thanks to recent achievements in understanding the causes of the cartilage degradation many therapeutic approaches are now being investigated ( Hochberg et al, 2019 ; Ghouri and Conaghan, 2019 ; Stevens et al, 2019 ; Thorup et al, 2020 ; Yazici et al, 2020 ; Fernández-Martín et al, 2021 ). However, we cannot hope for a structure-modifying treatment to be marketed for several years.…”
Section: Introductionmentioning
confidence: 99%